Association of two groups of phytoplasma with various symptoms in some wooden and herbaceous plants. Issue 4 (29th January 2018) - Azimi, Mohammad; Mehrabi‐Koushki, Mehdi; Farokhinejad, Reza
Abstract: During 2015–2016, wooden and herbaceous plants growing in parks, boulevards, fields, gardens and forests in Khuzestan province, southwestern Iran, were visually inspected for symptoms resembling phytoplasma. Fifty‐one symptomatic samples from nine different species and one symptomless sample from each plant were collected. Leaf midribs, petioles and the parts of stem cambium were separated and freeze‐dried. Total DNA was extracted using CTAB‐based method and tested for phytoplasma using a nested PCR assay. The expected size amplicons of 16S rDNA were sequenced and compared to those of reference phytoplasmas by BLASTn search and phylogenetic analysis. The consensus 16S rDNA sequence of the detected phytoplasma in narrow cattail related to reference phytoplasma group 16SrVI, " Candidatus Phytoplasma trifolii" while in the other plants were related to reference phytoplasma subgroup 16SrII–D, " Candidatus Phytoplasma aurantifolia." All isolates showed 98%–99% sequence identity to members of their reference groups. To our knowledge, this is the first report of " Candidatus Phytoplasma aurantifolia"‐related strains infecting the plants of Acacia salicina, Alternanthera ficoidea, Melaleuca citrine, Citrus aurantium throughout the world and Celosia christata in Iran. Furthermore, this study is the first to report the association of a " Candidatus Phytoplasma trifolii"‐related strain with Typha angustifolia worldwide.